Academic Senate Minutes 2014-09-25 - Academic Senate:::::::::
Agenda Approved. Minutes of 8/28 and 9/11 – Approved. Provost Report. Vice Chair Report. Questions for the Vice President of Administration and Finance. Vice President of Student Affairs Report. Associated Students Report. Statewide Senator Report. EPC Report. FSAC Report. Request for endorsement for Sustainability Executive Committee Vision, Missions and Goals – endorsement approved. SAC Report. CFA Report. Resolution regarding the location of the 2014 Academic Conference from the floor – Approved. Senate input on Smoking Policy change. Request for Feedback on Statewide Student Success Fees. Good of the Order.